2002
DOI: 10.1079/ber2001149
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation and habitat use by Lucilia blowflies (Diptera: Calliphoridae) in pasture

Abstract: The spatial distribution of blowflies of the genus Lucilia within fields in south west England was examined in 1999 and 2000. Blowflies are economically important agents of sheep myiasis in the UK and understanding local aggregation is an essential step in the development of appropriate sampling and fly control regimes. Fifty, 20 x 20 cm, non-odour-baited, sticky traps were used to catch flies, at randomized, 10 x 10 m grid co-ordinates in fields of permanent pasture. Clear aggregations were evident in all Luc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
(23 reference statements)
1
3
0
Order By: Relevance
“…The Breeding Center is located in the Qinling Mountains with dense forest and an altitude of 1496 meters. At the time of this case, it was summer with warmer and more humid, which is in line with the preferred habitat of the L. caesar [32].…”
Section: Discussionsupporting
confidence: 71%
“…The Breeding Center is located in the Qinling Mountains with dense forest and an altitude of 1496 meters. At the time of this case, it was summer with warmer and more humid, which is in line with the preferred habitat of the L. caesar [32].…”
Section: Discussionsupporting
confidence: 71%
“…From this point of view, air temperature seems to be particularly important for the current results. It was found that ambient air temperature is a positive predictor for visitation on non-odor sticky traps by adult Lucilia flies [ 47 ] and for blowfly oviposition on a beef liver bait [ 37 ]. These results directly demonstrate that forensically relevant aspects of blowfly activity are mediated by temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Space and time are the two variables at the origin of all variation because, ultimately, even abiotic variability is driven by these variables. While time has been of great concern to forensic entomologists as evidenced by the importance of research on the postmortem interval, the period of insect activity [34] and the pre-appearance interval [35], space remains an essentially unexplored dimension (but see [5][6][7][8]). To our knowledge, this study presents the first analysis of regional spatial dynamics in forensic entomology.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, several parameters that are mostly abiotic in nature were extensively documented for their influence on the development of insect larval stages and on the progression of insect succession on necromass [1,2]. Spatial and scale effects, however, have barely been considered in forensic entomology [3][4][5][6][7][8], despite their pervasive effects on most of the biotic and abiotic parameters affecting insect occurrence and development. Space here refers to the place where the organisms involved in decomposition interact with each other and with the abiotic environment [9].…”
Section: Introductionmentioning
confidence: 99%